Natural Agents against Bovine Mastitis Pathogens - Zorana Kovačević; Miodrag Radinović; Ivana Čabarkapa; Nebojša Kladar; Biljana Božin (MDPI AG, 2021)
Bovine mastitis is the most widespread and economically important disease worldwide. The present study aimed to determine bioactive compounds in two essential oils (EOs) from wild (Thymus serpyllum) and common thyme (Thymus vulgaris) and to assess the antioxidant potential as well as antibacterial efficacy of the EOs against mastitis-associated bacteria. The study also included antibiotic susceptibility tests. The strains were previously isolated from lactating animals with clinical and subclinical mastitis. The antioxidant potential of the commercial EOs of wild and common thyme was evaluated by five in vitro assays. The antibacterial activity was performed using the microdilution technique, while antibiotic susceptibility testing was performed by the Kirby-Bauer disc diffusion method. The dominant compound in wild thyme was thymol (45.22%), followed by p-cymene (23.83%) and γ-terpinene (3.12%), while in common thyme, it was thymol (54.17%), followed by γ-terpinene (22.18%) and p-cymene (16.66%). Among the fourteen mastitis-associated bacteria, strain IX Streptococcus spp. (β-hemolytic) was the most sensitive to the tested EOs (minimum inhibitory concentration (MIC)/minimal bactericidal concentration (MBC) were 0.78/1.56 and 0.39/0.78 mg/mL for T. serpyllum (TS) and T. vulgaris (TV), respectively). Regarding Streptococcus spp. β heamoliticus, MICs for TS ranged from 0.78 to 1.56 mg/mL, while for the same oil, MBCs ranged from 1.56 to 12.5 mg/mL. In the case of T. vulgaris, MICs ranged from 0.39 to 3.125 mg/ mL, while MBCs ranged from 3.125 to 6.25 mg/mL. TV is more active against E. coli, E. sakazakii, and Streptococcus spp., while it is less effective against Staphylococcus spp. than TS. The study revealed that the tested EOs possess remarkable antioxidative and antibacterial activities and could be used in the development of pharmaceutical formulation as an alternative to conventional mastitis therapy.